CPC-049 Evaluation of a Standardised Therapeutic Education Training Session For Hypertensive Stroke Patients. (12th March 2013) - Vallet, C; Beaussier, H; Bruandet, M; Zuber, M; Bezie, Y; Tersen, I
Abstract : Background: A standardised therapeutic education (TE) intervention was developed in 2009 in the department of Neurology, for hypertensive stroke patients. This training session has been officially authorised (Agence Régionale de Santé) since 2011. Purpose: To assess the effectiveness of the TE training. Materials and Methods: The TE training is for hypertensive patients hospitalised in a stroke unit for a cerebrovascular accident (CVA), and treated with antihypertensive drugs, when they are able to participate. We performed: an evaluation of the patients' knowledge of hypertension (HT), self-measurement, and adherence to antihypertensive medicines, using a questionnaire (6 short questions) filled in before and after the TE session, during a consultation; an evaluation of patient satisfaction, with an opinion questionnaire (after the TE session). Results: 67 patients participated in at least one session. a) 18 patients took part in a second session during a consultation, on average 4 months after the first session. The pre- and post-TE questionnaires were compared, and a score calculated, for 11 patients (7 patients excluded). The total post-TE score was significantly improved (34 ± 7 vs. 43 ± 2; p = 0.005). All items' scores had increased significantly: link between HT and CVA (P = 0.05), possibility of treating HT (P = 0.03), adaptation to antihypertensive drugs (P = 0.006), regular blood pressure measurement (P = 0.05). The score about the continuation of antihypertensive treatment was the only one that did not improve significantly. Results for medicines adherence could not be analysed (many patients had no treatment before hospitalisation). Post-TE, more patients carried out regular self-measurement. b) We analysed 40 opinion questionnaires: 94% of patients were completely satisfied with the session (reception, timing, educator open to listening, clarity), 80% felt completely capable of applying what they learned, 83% said they were ready to take part in other sessions. Conclusions: These results are really encouraging, about increased knowledge and patient satisfaction. Space should be made for a second TE session in post-CVA consultations. No conflict of interest.